Legal Opinion : Nicaragua v. United States of America - Amadda Ilmi (Jurnal Hukum Lex Generalis, 2020)
This case occurred between the United States (USA) and Nicaragua, where the problem between the two is a dispute that led to allegations of violations of international law, starting from the problems of domestic government that occurred in the Republic of Nicaragua. However, the United States is actively involved in these internal issues. Nicaragua considers that the interference by the United States further worsens the state of nicaragua's government and feels that the United States has committed actions contrary to the rules of international law. One of his interventions was when the U.S. took steps to stop economic aid to Nicaragua because nicaragua had previously fought El Salvador, where El Salvador was known to have good diplomatic relations with the United States. Knowing this, the U.S. also made some kind of attack by sending its military on Nicaraguan territory and planting mines in the sea and inland sea of Nicaragua, causing ships to be damaged and even destroyed. The U.S. also conducted corporate civilian and military facilities in Nicaragua. Of course, this is very disturbing to Nicaragua, because it did not make any efforts against the Americans but came under attack for its case with El Salvador. The case was then reported to the ICJ who mediated and considered that the actions taken by the United States were wrong, because it was too into matters that did not include its jurisdiction to participate in the case.